Production of recombinant proteins in milk of transgenic and non-transgenic goats - Moura,Raylene Ramos (2011)
Among all the transgenic mammalians produced so far, goats have represented an excellent model of transgenesis when considering the factors such as the market demand for protein, volume of milk produced per lactation and reproductive rate. Various recombinant proteins have been obtained from the transgenic and non-transgenic goats, and among these, human antithrombin, produced by the transgenic goats, was the first recombinant protein of animal origin to be released as a drug for the clinical use in humans. This review reports the aspects inherent to the production of recombinant proteins in the goats, from the production of the animal bioreactors up to the expression of these proteins in their milk.